THE ROLE OF CERTIFICATION SCHEMES (RSPO, ISPO, MSPO) IN SHAPING GLOBAL PALM OIL MARKET ACCESS - Hamdani Hamdani (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study explores the role of palm oil certification schemes Roundtable on Sustainable Palm Oil (RSPO), Indonesian Sustainable Palm Oil (ISPO), and Malaysian Sustainable Palm Oil (MSPO) in shaping global market access for palm oil products. Using a literature review method, this research analyzes scholarly articles, policy papers, and industry reports to examine how sustainability certifications influence trade opportunities, supply chain governance, and international perceptions of environmental responsibility. The findings reveal that certification schemes function as both market entry mechanisms and instruments of environmental diplomacy. RSPO, as a voluntary global standard, often dominates international trade preferences, particularly in Europe and North America. Meanwhile, ISPO and MSPO represent national policy responses aimed at asserting sovereignty over sustainability governance and enhancing competitiveness in the global market. However, challenges remain in aligning these schemes with international expectations, particularly regarding traceability, compliance costs, and the inclusion of smallholders. The study concludes that harmonizing certification standards and strengthening transparency across supply chains are essential to improving the global acceptance of certified palm oil. Furthermore, literature suggests that future policy integration between public and private standards could enhance mutual recognition and promote sustainable trade practices globally.